SPECTRUM OF CLINICAL AND HAEMATOLOGICAL FINDINGS IN MALARIA - Jawad Zafar Chaudry; Khalid Mahmood; Muhammad Altaf Hussain; Muhammad Uzair Ilyas Tahirkheli (Gomal Journal of Medical Sciences, 2015)
Background: Malaria is commonly associated with various clinical and haematological findings. The study was conducted to evaluate clinical and haematological findings in common types of malaria. Material & Methods: This descriptive study was conducted in Combined Military Hospital, Dera Ismail Khan, from August 2013 to December 2013. A total of 200 malaria patients confirmed on microscopy of Leishman stained peripheral blood films were included in the study. Complete blood count was carried out using Sysmex KX-21 automated hematology analyzer and thin blood smears were used for microscopy. The research variables were clinical and hematological findings. Data were analyzed by using statistical package for social sciences (SPSS) version 17.0. Results: Fever was present in all patients, associated with rigors and chills in 143(71.5%) patients and spleen was palpable in 139(69.5%) patients. P. vivax was found in 162(81%) and P. falciparum in 38(19%) patients. Anaemia was associated more with P. falciparum malaria where it was found in 77.8% patients in contrast to 47.3% with P. vivax where it was found in 45.1% patients while 16.7% patients with P. falciparum malaria were lymphocytopenic (p=0.02). Thrombocytopenia was present in 176 (88%) patients without statistically significant difference between the two species. Conclusion: Fever with rigors, chills and splenomegaly are the main clinical feature. While anaemia, thrombocytopenia and lymphocytopenia are major haematological features in malaria.